Pengaruh motivasi dan budaya organisasi terhadap disiplin kerja karyawan pada Hotel Mutiara Pekanbaru - Riznando Fadil; Machasin '; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this study was to analyzethe influence of organizational culture on motivation and discipline employees working at Mutiara Hotel Pekanbaru. To find outwhich is the most dominant factor that canaffect the discipline of employees working at Mutiara Hotel Pekanbaru. This research was conductedat the Mutiara Hotel Pekanbaru. The number of samples in this study wereas many as 98 employees Mutiara Hotel Pekanbaru using the technique of Simple Random Sampling technique. Data analysis techniques used in this research is descriptive statistic alanalysis techniques and inferential statistic analysis. Based on the results of the study indicate that 1) organizational culture and motivation together significantly influencethe employee's discipline Mutiara Hotel Pekanbaru. 2) Organizational culture significantly influences employee discipline. Motivation significantly influence work discipline. Motivation showed more dominant influence in determining the changes thatoccur inthe employee discipline Mutiara Hotel Pekanbaru when compared with theculture of the organization.Keywords: Motivation, organizational culture, work discipline